Ketogenic Diet-Induced Severe Ketoacidosis in a Lactating Woman: A Case Report and Review of the Literature. (8th July 2019) - Nnodum, Benedicta Nneoma; Oduah, Eziafa; Albert, David; Pettus, Mark
Abstract : The ketogenic diet (KD) is a high-fat, adequate-protein, and low-carbohydrate diet that leads to nutritional ketosis and weight loss. It is known to induce ketosis but is not an established cause of clinically significant ketoacidosis. Lactation ketoacidosis is well established in bovine literature but remains a rare phenomenon in humans. Here we present a life-threatening case of severe ketoacidosis in a nondiabetic lactating mother on a strict ketogenic diet. We review the available case reports of lactation ketoacidosis in humans and the mechanisms thereof. Although ketogenic diet has been shown to be safe in nonpregnant individuals, the safety of this diet in lactating mothers is not known. Health professionals and mothers should be made aware of the potential risk associated with a strict ketogenic diet when combined with lactation. Prompt diagnosis and immediate treatment cannot be overemphasized. To our knowledge, this is the first reported case of life-threatening lactation ketoacidosis associated with ketogenic diet while consuming an adequate number of calories per day.